Irinotecan and temozolomide for treatment of neuroblastoma in a patient with renal failure on hemodialysis. Issue 5 (23rd November 2013) - Armstrong, Amy E.; Dargart, Jamie; Reichek, Jennifer; Walterhouse, David O.; Matossian, Debora; Cohn, Richard A.; Gosiengfiao, Yasmin
Abstract Renal failure is a rare complication of neuroblastoma or its therapy. To our knowledge, no reports describe treatment of children with neuroblastoma with chemotherapy in the setting of renal failure and maintenance hemodialysis. We report a 6‐year‐old child with high‐risk neuroblastoma who developed renal failure requiring long‐term hemodialysis. She was subsequently treated with 13 cycles of intravenous irinotecan 20 mg/m2/day and oral temozolomide 100 mg/m2/day for 5 days before disease progression without any dose adjustments, transfusions, febrile neutropenia or diarrhea. This case demonstrates that irinotecan and temozolomide can be safely administered in children with renal failure requiring hemodialysis. Pediatr Blood Cancer 2014;61:949–950. © 2013 Wiley Periodicals, Inc.